Desmoplastic melanoma presenting as pyogenic granuloma: Report of a case with review of literature - Ratnam B (Wolters Kluwer Medknow Publications, 2010)
An elderly female patient was referred to the author for the treatment of a large recurrent pyogenic granuloma in the sole of right foot for a period of 2 years. She underwent excisional surgeries at an outside facility twice in the past. This time, she was treated with wide excision biopsy and the surgical defect was closed with a new technique, the "adjustable suture technique". Histopathology report confirmed "desmoplastic melanoma" with complete marginal clearance. The wound had healed uneventfully. There were no recurrences at 4-year follow-up.